Anatomy of Issa-Afar Violence. Issue 3 (September 2017) - , Muauz Gidey
Issa-Afar violence has often been viewed from instrumentalist and positivist perspective focusing on its use for a specific end and on its visible and agentive war violence per se. The dominate explanation has been resource oriented; specifically, conflict over scarce pastoralist resources and territory. However, this article contends that Issa-Afar violence has moved far away from substantive and originating issues that instrumentalist and positivist explanation and interventions informed by the same no longer explain the dynamics of violence. Because critical analysis of the anatomy of Issa-Afar violence reveals that the continuity of violence is owing to structural and cultural violence than substantive issues.